EGFR/TKIs induce excessive apoptosis of bladder carcinoma cells by arresting cell cycle and promoting mitochondrial peroxidation damage: Effect of EGFR-TKIs on bladder carcinoma - Yu, Xiaodong; Liao, Bo; Du, Zhongbo; Zhu, Pingyu (Cellular and Molecular Biology, 2024)
In recent years, bladder carcinoma (BC) has shown an increasing incidence, with poor patient outcomes. In clinical practice, BC is still mainly treated by surgery combined with chemoradiotherapy. However, as chemotherapy resistance of tumor cells becomes more and more obvious, it is urgent to find more effective BC treatment regimes. With the increasing application and growing attention paid to epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) in various neoplastic diseases, EGFR-TKIs have been considered as a new treatment direction in the future. In this study, the research team used AG1478, an EGFR-TKI, to intervene with the BC cell line T24. It was found that the cell activity was statistically decreased, the apoptosis was enhanced, and the cells were dominantly arrested in the G0/G1 phase, confirming the future therapeutic potential of EGFR-TKIs in BC. Besides, the research team further observed that AG1478 also promoted pyroptosis in T24 cells, and its mechanism is related to the induction of mitochondrial oxidative stress damage. The findings lay a more reliable foundation for the future application of EGFR-TKIs in BC.